Peranan Manufacturing And Accounting Buana System Terhadap Pengendalian Persediaan Barang Jadi Pada PT Cahaya Buana Intitama - Gustomi, Eka; ., Triandi (Institut Bisnis dan Informatika Kesatuan, 2014)
Inventory is an important part of the company's assets that every day experience changes that require a control system. At manufacturing, inventory control must be carried out effectively and efficiently, so that the company's operations to run optimally. This should be supported by an integrated control system of the manufacturing company. in this era of globalization, all companies in general have used computer-based information systems. The purpose of this study was to evaluate the MABS program as a system of information in controlling inventory of finished goods. Evaluation was conducted to determine whether the program MABS in controlling inventory of finished goods was effective and efficient, and evaluate about the admission procedure and finished goods expenditure. Research by the author is in PT Cahaya Buana Intitama located in Sentul, Bogor. PT Cahaya Buana Intitama a manufacturing company as a manufacturer of furniture products. The results showed that PT Cahaya Buana Intitama MABS program has been implemented effectively and efficiently in controlling inventory of finished goods. It is in view of the admission procedures and expenditures so goes according to pre-defined system, the procedure also pengoperasiaan MABS program has berjlalan optimally. MABS program can also provide complete information, quickly and accurately in accordance with company requirements. This program can also make the company's financial statements. Evaluation results of this research show that there are some things that must be considered by PT Cahaya Buana Intitama, namely the placement of data entry space less effective, it should be placed at the entrance and exit of goods, is not placed on the area, this will result in potential break-out goods in and goods out. Not maximal protection system on the MABS program that will result in the data input errors, and could affect the reporting of finished goods inventory, also can affect the company's financial reporting, then it should be added to the system of protection of the MABS program. Thus can minimize data input errors